3D Bioprinting at the Frontier of Regenerative Medicine, Pharmaceutical, and Food Industries - Ramadan, Qasem; Zourob, Mohammed (Frontiers in Medical Technology, 2021)
3D printing technology has emerged as a key driver behind an on-going paradigm shift in the production process of various industrial domains. The integration of 3D printing into tissue engineering, by utilizing life cells and hydrogels as bioinks, is paving the way towards devising many innovating solutions for key biomedical and healthcare challenges and heralds’ new frontiers in medicine, pharmaceutical industries. Here, we present a synthesis of the available 3D bioprinting technology from what is found, what has been achieved in various applications, and discussed the capabilities and limitations encountered in the technology.